Nonalcoholic fatty liver disease in asymptomatic obese women(a)(a)The work was originated in the Biomedical Research Unit of The Mexican Social Security Institute at Durango, Mex. - Heriberto Rodriguez-Hernandez (Annals of Hepatology, 2010)
Objective. To determine the clinical characteristics of NAFLD in asymptomatic obese women.Methods. A total of 457 asymptomatic obese women were enrolled in a cross-sectional study and allocated into groups with and without NAFLD. Irrespective of ALT levels, diagnosis of NAFLD was established by ultrasonographic findings; irrespective of fibrosis, NASH was defined by hepatic histological changes.Results. One hundred ninety five (42.7%) women had elevated ALT levels. Diagnosis of NAFLD was established in 228 (49.9%) women; among women with NAFLD, 34 (14.9%) have ALT levels within the normal range. On the other hand, based on the healthy range for ALT levels (19 UI/L), 336 (73.5%) women had elevated ALT, but only 2 (0.9%) women with NAFLD exhibited ALT levels within normal healthy values. Furthermore, 93 (41%) women who had AST/ALT levels 3 1 underwent liver biopsy; of these, 90 (96.8%) had diagnosis of NASH and 3 (3.2%) of hepatic cirrhosis. Women with NAFLD were more obese and have higher fasting plasma glucose, triglycerides, ALT, and AST levels than obese women without NAFLD. Seventy six (16.6%) women had diagnosis of diabetes; of these 47 (61.8) in the NAFLD group.Conclusions. Results of this study support the statement that women with NAFLD have an adverse metabolic profile. Furthermore, our results show that hyperglycemia, hypertriglyceridemia and markers of liver injury such as AST/ALT ≥ 1 may be useful for early recognition of NAFLD.